Atrial fibrillation in children: Case study - A. Samik Wahab, A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
Atrial fibrillation is very rare in children. Two children are described, although both were initially in congestive heart failure due to active carditis and were difficult to manage, but all have completely recovered. In addition to digitalis therapy all cases had quinidine, with therapeutic goal of controlling the heart rate rather than abolishing the fibrillation. One case died at home, 12 days after discharge from hospital and one recovered from fibrillation until now.Mitral and tricuspidal an nuloplasty have been performed to the second case, and the result is very satisfactory.Key Wards: atrial fibrillation Ã¢â¬â rheumatic hear t diseases Ã¢â¬â rheumatic feverÃ¢â¬â congestive heart failure Ã¢â¬â quinidine therapy